Determinação direta de halogênios em alumina, carvão e coque de petróleo por GF mas com amostragem de sólidos - Flores, Éder Lisandro de Moraes (2010)
Methods for fluorine (F) and chlorine (Cl) determination by molecular absorption spectrometry with graphite furnace vaporization and solid sampling (DSS-GF MAS) were developed. The developed methods were applied for F determination in coal and alumina and Cl determination in petroleum coke. As a preliminary treatment, the samples were grounded (<100 m, except to the alumina samples) and dried at temperatures ranging from 80 to 105 ºC. The determinations of F and Cl by DSS-GF MAS technique is based on the molecular absorption measures from the diatomic molecules AlF and AlCl, wich are generated in the vaporization step in the presence of an excess of Al in relation to F and Cl present in the sample. The furnace heating programs were optimized which consists of the following steps: drying (600 ºC for F and Cl), pyrolysis (F: 800 ºC, Cl: 700 ºC) and vaporization (F: 2300 ºC, Cl: 2100 ºC). The measurements of integrated absorbance were made at 227,5 nm for AlF and 261,4 nm for AlCl using hallow cathode lamps of Pt and Pb as radiation source, respectively. In order to prevent losses of F and Cl during the pyrolysis step, it is necessary the addition of chemical modifiers (10 Direct determination of halogen in alumina, coal and petroleum coke by gf mas with solid sampling Ba2+ for F and 20 g Sr2+ for Cl). The pyrolysis and vaporization temperatures for F and Cl were established with use of aqueous reference solutions and solid samples. By using the optimized conditions it was possible the determination of F and Cl based on the calibration with aqueous reference solutions. The accuracy of the methods was evaluated by analyzing certified reference materials and by comparison with results obtained by independent methods. No statistical significant difference at a confidence level of 95% was observed between results obtained and certified values or the results obtained by independent methods. The detection limits for F and Cl were 100 pg and 200 pg, respectively. Calibration curves were linear from 1 to 20 ng and from 20 to 80 ng (using mini-flow in the vaporization step) for F and from 1 to 25 ng for Cl. This is the first time that DSS-GF MAS was applied for F and Cl determination. Besides, the developed methods are simple to be applied to complex matrix for F and Cl determination due to the direct introduction of samples and by not requiring no prior stage of sample decomposition.